Implementation Of Sbar Communication In Nursing Practice To Improve Patient Safety - Ardianto Ardianto; Tri Ayu Yuniyanti; Suratno Kaluku; Moh. Nisyar Sy. Abd. Azis; Zulfikar Peluw (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Patient safety (patient Patient safety is a top priority in healthcare. One contributing factor to patient safety incidents is ineffective communication between healthcare workers. The SBAR (Situation, Background, Assessment, Recommendation) communication method was developed as a structured communication tool to improve the clarity and accuracy of clinical information. This study aims to analyze the implementation of SBAR communication in nursing practice and its impact on improving patient safety. safety. The study used a quantitative design with a cross-sectional approach. The study sample consisted of 60 nurses working in the inpatient ward of Hospital X, selected using a purposive sampling technique. Data were collected using an SBAR implementation questionnaire and a patient safety incident observation sheet. Data analysis was performed univariately and bivariately using the Chi- Square test. The results showed that good SBAR communication implementation was significantly associated with increased patient safety (p < 0.05). It was concluded that SBAR communication is effective in supporting safe and quality nursing practices.